Low-dissipation heat devices: Unified trade-off optimization and bounds - de Tomas, Carla Mercedes; Roco, J.; Hernández, A.; Wang, Y.; Tu, Z. (The American Physical Society, 2013)
We apply a unified and trade-off based optimization for low-dissipation models of cyclic heat devices which accounts for both useful energy and losses. The resulting performance regime lies between those of maximum first-law efficiency and maximum ? (a unified figure of merit corresponding to power output of heat engines). The bounds available for both symmetric and extremely asymmetric heat devices are explicitly obtained. The similarities for heat engines and refrigerators and the energetic advantages of the trade-off optimization are especially stressed. © 2013 American Physical Society.